1993
DOI: 10.1111/j.1365-2958.1993.tb02673.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome bd biosynthesis in Escherichia coli: the sequences of the cydC and cydD genes suggest that they encode the components of an ABC membrane transporter

Abstract: At least four genes are known to affect formation of the cytochrome bd-type terminal oxidase of Escherichia coli. In addition to the genes (cydA and cydB) encoding the two constituent subunits of this complex, a further two genes (cydC and cydD) map near 19 min on the E. coli chromosome. We report here the cloning of both genes on a 5.3 kb ClaI-HindIII restriction fragment, which, when used to transform either a cydC or cydD mutant, restored the ability of these mutants to grow on a selective medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 33 publications
2
90
0
Order By: Relevance
“…This family may also include YojI, which has a similar domain organization and a TMD closely related to the TMDs of the other members of the family, although the ABC domain of YojI is either of different origin or has diverged faster than the other members of the subfamily. No clear function for any of these proteins has been defined, although CydCD is required for biogenesis of cytochrome oxidase b (Poole et al, 1993). However, members of this family are the E. coli proteins most closely related to the mammalian multidrug resistance P-glycoprotein and the multidrug resistance protein of Lactococcus lactis, LmrA (van Veen et al, 1998).…”
Section: Function/substrate Specificitymentioning
confidence: 99%
“…This family may also include YojI, which has a similar domain organization and a TMD closely related to the TMDs of the other members of the family, although the ABC domain of YojI is either of different origin or has diverged faster than the other members of the subfamily. No clear function for any of these proteins has been defined, although CydCD is required for biogenesis of cytochrome oxidase b (Poole et al, 1993). However, members of this family are the E. coli proteins most closely related to the mammalian multidrug resistance P-glycoprotein and the multidrug resistance protein of Lactococcus lactis, LmrA (van Veen et al, 1998).…”
Section: Function/substrate Specificitymentioning
confidence: 99%
“…First, mutants defective in cydC or cydD encoding the polypeptides of the heterodimer, exhibit several defects of the periplasm, namely a hyperoxidized redox state and failure to assemble periplasmic cytochromes b and c (40,41). Second, cydDC mutants fail to assemble the cytochrome bd-type oxidase complex (25,41); in such mutants, the CydA and CydB subunits are detectable but the hemes are not incorporated into the subunits (42). Interestingly, both the hemes and the oxygen-reactive site (43) are thought to be close to the periplasmic side of the cytoplasmic membrane.…”
Section: Gsh Is Transported By Cyddc In An Atp-dependent Manner-the Ementioning
confidence: 99%
“…DTT was therefore first removed by solvent extraction with ethyl acetate, and the GSH was then oxidized to GSSG by exposure to air for 24 h. To determine whether the oxidation was complete, we employed DTNB, which undergoes oxidation in the presence of sulfhydryl groups. The transport assay conditions used to determine [ 35 (25) and periplasmic cytochromes c (41). Because GSH is a substrate of the CydDC transporter, it may be directly required in cytochrome bd assembly.…”
Section: Gsh Complements Bacterial Motility Defects In a Cydd Mutant-wementioning
confidence: 99%
See 1 more Smart Citation
“…Deletion analysis indicated that an intact leucine-rich repeat (residues 345-470) of CCR4 was required for its interaction with both CAF4 and CAF16 (Table II, to encode a novel protein (yeast protein YKR036c) containing seven WD40 repeats in its C terminus (residues 320 -659). CAF16 when sequenced in its entirety was found to encode a protein (now designated YFL028c) that shares significant homology to the ABC ATPase family of proteins (31,32). ABC ATPases are principally found to play roles in transport across membranes and as membrane receptors (33).…”
Section: Ccr4mentioning
confidence: 99%